IMPLEMENTATION OF TB CONTROL POLICY: A CASE STUDY OF COMMUNICATION BARRIERS AND RESOURCE ALLOCATION IN THE CADRE EMPOWERMENT PROGRAM IN SOUTH TAPANULI REGENCY - Safran Efendi Pasaribu; Mukhlis Mukhlis; Putoro Dongoran; Pranjono Pranjono (Journal Analytica Islamica, 2026)
Tuberculosis (TBC) remains a significant public health challenge in Indonesia, which consistently ranks among the top three countries with the highest TBC burden globally. The government has set a TBC elimination target for 2030 through community empowerment as a subject of prevention. This study aims to analyze the implementation of TBC control policies with a focus on communication barriers and resource allocation in Batang Toru District, South Tapanuli Regency. Utilizing a descriptive qualitative approach with a case study design, this research applies George C. Edwards III’s implementation theory. Data were collected through technical triangulation, including in-depth interviews, field observations, and documentation studies. The results indicate significant communication barriers in the form of message distortion due to the use of overly technical medical terms, which are difficult for health cadres to translate into the local language (Batak Angkola). Furthermore, constraints were found in resource allocation, including the phenomenon of "volunteer fatigue" due to multiple roles, minimal financial incentives, and limited supporting facilities such as personal protective equipment and local educational media. Weak budgetary support from Village Funds and a lack of cross-sector synchronization with the private sector in industrial areas further hinder program optimization. This study recommends a redesign of communication materials based on local wisdom, stricter integration of Village Fund allocations, and strengthening strategic partnerships with the private sector through CSR programs to support the sustainability of TBC control programs at the local level